Photopatch and UV-irradiated patch testing in photosensitive dermatitis - Reena Rai; Maria Thomas (Wolters Kluwer Medknow Publications, 2016)
Background: The photopatch test is used to detect photoallergic reactions to various antigens such as sunscreens and drugs. Photosensitive dermatitis can be caused due to antigens like parthenium, fragrances, rubbers and metals. The photopatch test does not contain these antigens. Therefore, the Indian Standard Series (ISS) along with the Standard photopatch series from Chemotechnique Diagnostics, Sweden was used to detect light induced antigens. Aim: To detect light induced antigens in patients with photosensitive dermatitis. Methods: This study was done in a descriptive, observer blinded manner. Photopatch test and ISS were applied in duplicate on the patient's back by the standard method. After 24 hours, readings were recorded according to ICDRG criteria. One side was closed and other side irradiated with 14 J/cm2 of UVA and a second set of readings were recorded after 48 hrs. Result: The highest positivity was obtained with parthenium, with 18 out of 35 (51%) patients showing a positive patch test reaction with both photoallergic contact dermatitis and photoaggravation. Four patients (11%) showed positive patch test reaction suggestive of contact dermatitis to potassium dichromate and fragrance mix. Six patients had contact dermatitis to numerous antigens such as nickel, cobalt, chinoform and para-phenylenediamine. None of these patients showed photoaggravation on patch testing. Conclusion: Parthenium was found to cause photoallergy, contact dermatitis with photoaggravation and contact allergy. Hence, photopatch test and UV irradiated patch test can be an important tool to detect light induced antigens in patients with photosensitive dermatitis.